El llenguatge sexual i la vergonya femenina segons Francesc Eiximenis. - RENEDO, XAVIER (Scripta, 2014)
This paper analyses Francesc Eiximenis' advice and commentary with regards to sexual language: modesty, particularly concerning women; obscene language as well as euphemisms, circumlocution and periphrasis to avoid it; the measure of sexual pleasure; or the menstrual flow. Finally, a case of censorship in one of the manuscripts witnessing Eiximenis' Terç del Crestià is discussed as possibly triggeredby the application of these concepts.